EDUKASI BIO-FORENSIK : SOSIALISASI PENCEGAHAN PENYAKIT DAN PEMERIKSAAN KESEHATAN DASAR - Egita Windrianatama puspa; Gustiadi Saputra (LPPM Universitas dr. Soebandi, 2026)
Vector-borne diseases remain a public health concern closely related to environmental conditions and community behavior. Limited public awareness regarding environmental management and disease prevention contributes to the persistence of vector breeding sites. This community service activity aimed to increase public understanding and awareness of vector-borne disease prevention through health socialization, basic health screening, and environmental control education. The activity was conducted in Wayakrui Village, Banyumas Subdistrict, Pringsewu Regency, using a participatory and promotive–preventive approach. The methods included health education sessions, basic health screening through blood pressure measurement, and distribution of larvicide (abate) accompanied by education on proper use. The results showed positive community participation and engagement during the activities, reflected in active discussions, interest in environmental risk factors, and improved understanding of vector control measures. The integration of health education and basic health services supported effective communication and increased community awareness regarding disease prevention. In conclusion, community-based health socialization combined with basic health screening can support efforts to improve public awareness and understanding of vector-borne disease prevention and environmental health management.